2017
DOI: 10.1155/2017/9684193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Pediatric Drugs on the Color Stability of Various Restorative Materials Applicable in Pediatric Dentistry

Abstract: Background. The chronic recommendation of pediatric drugs could exhibit erosive and cariogenic problems. Objective. To evaluate the effects of different pediatric drugs on the color stability of various restorative materials. Methods. Five specimens (1 mm × 3 mm) were prepared and immersed in ten different pediatric drugs and agitated every 8 hours daily for 2 min up to 1 week. Between immersion periods, the samples were stored in artificial saliva. After 1-week period, ΔE⁎ values were calculated. Two-way ANOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 23 publications
1
25
1
Order By: Relevance
“…In contrast to our findings, previous studies evaluating the color stability of pediatric restorative materials showed that the composite is the least color-stable material [ 12 , 20 , 28 , 33 ]. Our results show that a significant change in color in the amoxicillin composite, amoxicillin GIC, and ventolin GIC groups, which is inconsistent with the results of previous studies, might be due to a variety of factors, including the presence or absence of the brushing component, the difference in the experiment’s duration, the medications utilized and their pH levels, the brands of the materials used, or the surface roughness.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, previous studies evaluating the color stability of pediatric restorative materials showed that the composite is the least color-stable material [ 12 , 20 , 28 , 33 ]. Our results show that a significant change in color in the amoxicillin composite, amoxicillin GIC, and ventolin GIC groups, which is inconsistent with the results of previous studies, might be due to a variety of factors, including the presence or absence of the brushing component, the difference in the experiment’s duration, the medications utilized and their pH levels, the brands of the materials used, or the surface roughness.…”
Section: Discussioncontrasting
confidence: 99%
“…To avoid air entrapment and voids, a cellulose acetate matrix strip was placed over the ring and held between two 1 mm thick glass slides. Three restorative materials were prepared according to the manufacturer’s instructions [ 28 ]. The compomer specimens were polymerized by applying a light-emitting diode (LED) polymerization light (3M ESPE Dental, Dublin, Ireland) of 1200 mW/cm 2 to each surface for 20 s, with the tip of the light unit on the glass slide (0 mm away from the specimen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Afzali assessed the effect of ingested liquids on the color change of composite resin; unlike the present investigation, they concluded that the discoloration values did not depend on the type of staining solution. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…The only study which involves the effect of pediatric syrup multivitamins on glass ionomer cements evaluated color stability. 19 Therefore, the aim of this study was to evaluate and compare the effect of two different pediatric multivitamin syrups and effervescent tablets taken daily for 28 days on the surface microhardness and roughness of two different restorative materials.…”
Section: Introductionmentioning
confidence: 99%